Uncertainty and Economic Activity: A Multicountry Perspective - Cesa-Bianchi, Ambrogio; Pesaran, M Hashem; Rebucci, Alessandro (Review of Financial Studies, 2020)
Abstract We develop an asset pricing model with heterogeneous exposure to a persistent world growth factor to identify global growth and financial shocks in a multicountry panel VAR in volatility and output growth. The econometric estimates yield three sets of empirical results about (1) the importance of global growth for the interpretation of the correlation between volatility and growth over the business cycle and the possible presence of omitted variable bias in single-country VAR studies, (2) the extent to which output shocks drive volatility, and (3) the transmission of volatility shocks to output growth. Authors have furnished data, code, and an Internet Appendix, which are available on the Oxford University Press Web site next to the link to the final published paper online.